Population‐based cohort study on the epidemiology of acute appendicitis in children in Sweden in 1987–2013. Issue 3 (19th April 2018) - Almström, M.; Svensson, J. F.; Svenningsson, A.; Hagel, E.; Wester, T.
Abstract : Background: The long‐term incidence of acute appendicitis has been reported to be declining in Europe and North America. Recent reports, however, indicate stabilized or even increased rates. The aim of this study was to investigate the present epidemiology of acute appendicitis and appendicectomy in a population‐based cohort of Swedish children. Methods: The Swedish National Patient Register was queried for all children with acute appendicitis and/or appendicectomy in 1987–2013. Population‐based incidence rates were calculated. Rates were age‐ and sex‐adjusted, and analysed for temporal and regional trends. Results: Some 56 774 children with acute appendicitis were identified, of whom 53 478 (94·2 per cent) underwent appendicectomy. The incidence rate of acute appendicitis declined by 43·7 per cent over 26 years, from 177·7 to 100·1 per 100 000 person‐years between 1987 and 2013. The most significant reduction was for non‐perforated appendicitis, from 138·5 to 68·4 per 100 000 person‐years between 1987 and 2009. The incidence rate of perforated appendicitis decreased from 28·0 to 19·9 per 100 000 person‐years and negative appendicectomies reduced from 48·5 to 3·6 per 100 000 person‐years during the study interval. Conclusion: The incidence rates of acute appendicitis and negative appendicectomy have reduced markedly in Swedish children over time, with significantly different trends amongst non‐perforated appendicitis and perforated appendicitis. The full explanation for the observed findings is unclear. Abstract : The epidemiology of acute appendicitis was investigated in a population‐based cohort of Swedish children. Incidence rates of overall acute appendicitis, appendicitis subtypes and negative appendicectomies were all markedly reduced over time. Age, sex and healthcare region all had an influence on rates and trends over time. Appendicitis on the decline